Groundwater investigation using the seismoelectric method - Rosid, Mohammad Syamsu (Curtin University, 2007)
Seismoelectric methods are based upon an energy conversion from mechanical energy into electromagnetic energy when seismic waves pass through rocks. The electrokinetic sounding (EKS) is one such method that has great potential to probe for hydrogeological studies as it results from the movement of pore fluids under seismic excitation. In theory, the method should be able to directly map changes in hydraulic permeability, rock porosity, or fluid-chemistry. The main purpose of this study is to test whether the seismoelectric response can be used to detect and map hydrogeology parameters such as changes of permeability, porosity, salinity, and thickness. This study is focused on survey design, approaches to reduce electronic and natural noise, and data processing techniques to combat ambient electromagnetic noise. The interpretation of data is another important component and guidelines and means to avoid processing artifacts and misinterpretation of ghost signals from multiple reflections. Pitfalls in the method were examined and approaches to enhance the acquisition method developed. In practice, the limited number of acquisition channels, and the strength of type 1 unwanted signals compared to the desired Type 2 signals limits the effectiveness of the f-k or τ-p filters. A solution to this problem was devised by combining shot records from 24 channels at different positions to perform a virtual 120 channels shot record. This composition allowed velocity or move-out dependent filters to perform more effectively.Field measurements were undertaken in three different areas in Western Australia that could be characterised as shallow and deep aquifers, saline and fresh groundwater, and impermeable and permeable medium. These field measurements produced two types of electrokinetic response; non-radiating field Type 1, and radiating field Type 2 seismoelectric effects. The interpreted results from these data sets demonstrate that the electrokinetic responses can be detected from formations more than 60 metres deep. Some significant hydrogeological boundaries were recorded up to 21 m deep over a paleochannel in saline groundwater conditions, and to at least 50 m deep in freshwater aquifers. Evidence is produced from these trials for electrokinetic signals arising from changes in permeability and fluid chemistry/salinity; thus supporting the basic theory of electrokinetic conversion, and providing further support to the assertion that electrokinetic conversion is a tool for hydrogeological investigation.